Influence of Store Atmosphere and Price on Costumer Loyality (Study at Diantara Kopi Coffee Shop in Bandung) - Hendiarto, R Susanto; Laksana, Rinda Febrianti; Alhafizh, Fikri (Politeknik Ganesha Medan, 2024)
Observing the last year, many coffee shops scattered across Bandung have experienced a significant increase in the number of coffee shops. There are many kinds of coffee shops in the Bandung area, ranging from manual brew coffee shops to those that serve iced coffee milk which is now the best seller along with a variety of other foods. Given the many facilities and infrastructure that coffee shops now provide, some people use them for various activities, including hangouts or just sessions with new friends, family or co-workers. This research tries to determine the store atmosphere and prices on customer loyalty. This research methodology uses an explanatory design by way of observation, surveys, and interviews. all kinds of data collection techniques. Validity test, reliability test, traditional assumption test, normality test, and multicollinearity test were used in data analysis. Multiple linear regression model for regression analysis. The research findings indicate that store atmosphere and prices can have an impact on Coffee customer loyalty both partially and simultaneously.